Sugihmanik Tofu Industry MSME Strengthening with Integrated Implementation of Biogas Energy Conversion to Electricity: Penguatan UMKM Industri Tahu Sugihmanik dengan Implementasi Terintegrasi Konversi Energi Biogas ke Listrik - Sri Hartini; Muchammad; Suroto Munahar; Dhimas Cahyo Anindito; Bagiyo Condro Purnomo (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
Sugihmanik, Tanggungharjo District, Grobogan Regency have tofu industry center with 30 Micro, Small, and Medium Enterprises (MSME). It is hoped that these MSMEs can improve the community's economy, but on the other hand they can also cause pollution problems for the environment. The waste produced in tofu processing production activities reaches an average of 67,997 m3/day from tofu production, with a total demand for soybeans of around 3200 kg/day. Some of this waste is thrown into rivers, which hurts the ecosystem in a chain that results in the death of aquatic animals, the agricultural environment, and unpleasant odors. Based on the problems in MSMEs, this activity proposes the technology design for converting biogas gas into electricity. The method to solve this problem is to utilize energy from tofu industry waste converted into electrical energy. In implementing biogas conversion technology, it can be tested with a partner electricity load of 1500 watts. However, this technology still has several obstacles. When changing modes, the generator machine for converting biogas into electrical energy requires a manual synchronization system. So, it requires training from partners. In the future, this activity will continue with the development of automatic synchronizing control systems, making it easier to use